Antioxidant properties of spice extracts - Wahyu Widowati (Biomedical Engineering, 2015)
Objective : This study was conducted to determine the antioxidant activities of spice extractsincluding clove (Syzygum aromaticum L.), Indonesian cassia (Cinnamomum burmanni (C. Nees& T.Ness)), coriander (Coriandrum sativum L), nutmeg (Myristica fragrans Houtt), java cardamom(Amomum compactum Soland. Ex maton).Methods : This research was to evaluate antioxidant activities including 1,1-diphenyl-2-picrylhydrazyl(DPPH) scavenging activity, the value of superoxide dismutase (SOD), and total phenoliccontent.Result : The highest DPPH activity is clove and Indonesian cassia extracts with IC50 value 4.16μg/ml and 5.46 μg/ml respectively. The highest SOD value are Indonesian cassia extract (9.1432U/ml) at 500 μg/ml, 7.0045 U/ml at 125 μg/ml and 4.6751 U/ml at 31,25 μg/ml. Clove extract was thehighest of phenolic content (188.35 μg/mg eugenol equivalent).Conclusion : Indonesian cassia extract have high antioxidant activities both DPPH scavenging andSOD activities. Clove extract contain the highest eugenol compared with Indonesian cassia,coriander, nutmeg and java cardamom.